2019
DOI: 10.1162/jocn_a_01359
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Neural Sources of Problem Size and Interference Effects in Multiplication

Abstract: Multiplication is thought to be primarily solved via direct retrieval from memory. Two of the main factors known to influence the retrieval of multiplication facts are problem size and interference. Because these factors are often intertwined, we sought to investigate the unique influences of problem size and interference on both performance and neural responses during multiplication fact retrieval in healthy adults. Behavioral results showed that both problem size and interference explained separate unique po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The complexity of multiplication depends on several factors (for an overview, see Domahs et al, 2006), for example, the interference effect (De Visscher and Noël, 2014). One other important factor is the effect of problem size (Tiberghien et al, 2018), i.e., multiplication problems with numerically larger operands are more difficult to solve—as reflected by higher reaction times (RT) and error rates (ER)—than multiplication problems with smaller operands (Verguts and Fias, 2005). While this effect can be derived from the neighborhood consistency when smaller single-digit problems (e.g., 3 × 4) are compared to larger single-digit problems (e.g., 8 × 7; Domahs et al, 2006; for the interacting neighbors model see Verguts and Fias, 2005), the problem size effect might be more pronounced when comparing problems with single-digit operands only (e.g., 4 × 6) to problems with at least one two-digit operand (e.g., 16 × 4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity of multiplication depends on several factors (for an overview, see Domahs et al, 2006), for example, the interference effect (De Visscher and Noël, 2014). One other important factor is the effect of problem size (Tiberghien et al, 2018), i.e., multiplication problems with numerically larger operands are more difficult to solve—as reflected by higher reaction times (RT) and error rates (ER)—than multiplication problems with smaller operands (Verguts and Fias, 2005). While this effect can be derived from the neighborhood consistency when smaller single-digit problems (e.g., 3 × 4) are compared to larger single-digit problems (e.g., 8 × 7; Domahs et al, 2006; for the interacting neighbors model see Verguts and Fias, 2005), the problem size effect might be more pronounced when comparing problems with single-digit operands only (e.g., 4 × 6) to problems with at least one two-digit operand (e.g., 16 × 4).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, complex arithmetic, which is typically solved by applying procedural strategies, requires a rather widespread fronto-parietal network, as it was observed in fMRI studies (e.g., Gruber et al, 2001; Fehr et al, 2007; Grabner et al, 2009a). Thereby, higher activation with increasing complexity in multiplication was observed in frontal areas such as the left inferior frontal gyrus (IFG) and left middle frontal gyrus (MFG), reflecting domain-general cognitive task demands (e.g., maintenance of rule-based decomposed calculation steps), and the posterior parietal cortex, reflecting domain-specific numerical task demands (Gruber et al, 2001; Grabner et al, 2007; Jost et al, 2009; De Visscher et al, 2015; see also Menon et al, 2000; Zago et al, 2001; Tiberghien et al, 2018). In EEG studies, more alpha desynchronization (decrease in alpha power) was observed for complex, non-retrieved arithmetic problems (Harmony et al, 1999; Moeller et al, 2010; but see Micheloyannis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We should note that the data reported here are part of a larger dataset; all results reported here are unique and address hypotheses that do not overlap with prior publications arising from this dataset (Tiberghien et al, 2019). Both the pre-scan and fMRI arithmetic tasks included three operations: multiplication, addition and subtraction.…”
Section: Tasksmentioning
confidence: 57%